Technosocial Challenges of the 21st Century: Practical Application of Transductive System-Network Methodology (TSNM) - Sayapin, Vladislav Olegovich (Философия и культура, 2025)
The modern stage of the development of the technosocial reality of the 21st century is increasingly characterized as a period of sharp complexity increase in systems, heightened turbulence, and unpredictability, accompanied by the emergence of unprecedented global threats and risks. A key factor generating this increased complexity, uncertainty, and loss of traditional predictability is the deep process of interdependent development of humans, society, and technological systems, which encompasses our entire civilization. The hybridity, nonlinearity, dynamism, and global scale of these issues make traditional disciplinary approaches (social constructivism, technological determinism) inadequate for their analysis and resolution, requiring a fundamentally new methodological optic. The theoretical foundation for overcoming this dichotomy is based on the concepts of G. Simondon (transduction and individuation), N. Luhmann (theory of social systems), and M. Castells (network society). Their complementary integration forms the core of the proposed methodology. The research methodology is based on the sequential application of four complementary methods that ensure analytical depth and systematic comparison of the concepts of Luhmann, Simondon, and Castells: the comparative-analytical method, the hermeneutic method (deep interpretation), the method of theoretical synthesis and conceptual integration, and historical-philosophical reconstruction and contextualization. The methods are chosen to not only conduct a detailed comparison but also to adequately work with very different types of theories (the highly abstract systemic theory of Luhmann, Simondon's ontology of technology, and Castells' sociological theory). In response to this need, a transductive systemic-network methodology (TSNM) is proposed, representing a new class of complementary research strategies. Its novelty lies in the synergistic application of three perspectives: transduction (G. Simondon) for analyzing the emergence and materiality of technosocial hybrids, systemic theory (N. Luhmann) for understanding autopoiesis and unintended consequences in complex systems, and network analysis (M. Castells) for identifying power relations and inequality in the "space of flows." The practical value of TSNM lies in its ability to: 1) provide a comprehensive analysis of complex technosocial issues; 2) identify points of risk and opportunity; 3) inform ethical technology design (Ethics by Design) and lead the development of adaptive regulation and strategies for ensuring safe and equitable development. TSNM serves as an indispensable tool for navigating and consciously shaping the technosocial future.